2020
DOI: 10.3390/antibiotics9030102
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glucosyltransferase Activity and Glucan Production as an Antibiofilm Mechanism of Lemongrass Essential Oil against Escherichia coli O157:H7

Abstract: The resistance of Escherichia coli O157:H7 to disinfection is associated with its ability to form biofilms, mainly constituted by glucans produced by glucosyltransferases. Citral and geraniol, terpenes found in the essential oil of Cymbopogon citratus (EO), have proven antibacterial activity against planktonic E. coli; however, no information was found about their efficacy and mode of action against E. coli biofilms. Therefore, the inhibitory effect of C. citratus EO, citral, and geraniol on glucans production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…Seixas et al [ 28 ] reported the same result at 0.25, 0.5, 0.75, 1, and 1.25 mg/mL C. citratus essential oil. A number of studies have reported these high proportions of the two isomers α-citral and β-citral in C. citratus essential oils, even when collected from different countries [ 33 , 34 , 35 , 36 , 37 ], as also confirmed by the present study. Brügger et al [ 38 ] reported that in addition to the high proportion of citral, their commercial C. citratus essential oil showed relevant amounts of nonan-4-ol (6.5%) and camphene (5.2%).…”
Section: Discussionsupporting
confidence: 90%
“…Seixas et al [ 28 ] reported the same result at 0.25, 0.5, 0.75, 1, and 1.25 mg/mL C. citratus essential oil. A number of studies have reported these high proportions of the two isomers α-citral and β-citral in C. citratus essential oils, even when collected from different countries [ 33 , 34 , 35 , 36 , 37 ], as also confirmed by the present study. Brügger et al [ 38 ] reported that in addition to the high proportion of citral, their commercial C. citratus essential oil showed relevant amounts of nonan-4-ol (6.5%) and camphene (5.2%).…”
Section: Discussionsupporting
confidence: 90%
“…Only the C. verum leaf EO, MIC and MBC values were not very different. As reported in previous papers [6,16,19,30,34,36,37], all EOs used in this study had an inhibitory effect on the planktonic growth of E. coli O157:H7, with some differences in strength of action. In addition, we reported that C. verum bark EO had a bactericidal effect on all strains used at a very low concentration (between 0.02% and 0.08% v/v), a finding supported by the work of Sheng et al [6] where C. verum EO was found to be bactericidal on E. coli O157:H7 at 0.05% (v/v).…”
Section: Antibacterial and Antibiofilm Activity Of Eossupporting
confidence: 77%
“…As reported in other investigations, essential oils represent an important source of compounds active against pathogens of public health interest, especially antibiotic-resistant strains. The EOs’ inhibition of bacterial growth could be due to the capacity to degrade membrane proteins and to increase cell permeability [ 38 ]. Moreover, EOs are active in the early stages of biofilm formation, inhibiting the adhesion of bacterial cells or interfering with quorum sensing [ 39 ], a system of bacterial communication that controls biofilm formation, antibiotic resistance, and expression of virulence factors.…”
Section: Discussionmentioning
confidence: 99%